Outlook for Interest Rates and Japanese Banks' Risk Exposures under Abenomics - Arslanalp, Serkan (IMF Working Papers; Working Paper ;, 2013)
This paper examines how Japan's long-term interest rates and Japanese banks' interest rate risk exposures may evolve under Abenomics. Results from a panel regression analysis for major advanced economies shows that long-term government bond yields in Japan are determined to a large extent by growth and inflation outlook, fiscal conditions, demography, and the investor base of government securities. A further deterioration of fiscal conditions would push up long-term rates by about 2 percentage points over the medium term, but the rise is partly offset by higher demand for safe assets amid population aging and increased purchases by the Bank of Japan. At the same time, illustrative scenarios suggest the interest rate risk exposure of Japanese banks could decline substantially over the next two years. However, if structural and fiscal reforms are incomplete, both long-tem yields and interest-risk exposures of Japanese banks could increase over the medium term.